Recovery of Acute Ophthalmoplegia after Hyaluronic Acid Filler Injections to the Temples: A Case Report and Review of the Literature - Tabatabaei, Fatemeh-sadat; Azimi, Amirali; Tabatabaei, Seyyed Shahabeddin; Pakdaman, Hossein (Archives of Plastic Surgery, 2023)
Soft tissue filler injection is the second most common nonsurgical cosmetic procedure. Despite the safety of fillers, as use has grown, so has the number of patients affected by adverse events. Ophthalmoplegia following cosmetic filler injection is a rare complication, mostly occurring after injection to the glabella, nasolabial fold, periorbital, and lateral nasal site. In all cases where ophthalmoplegia has been reported following fillers, patients have simultaneously experienced vision loss and other ocular symptoms. We report a case of isolated acute ophthalmoplegia following hyaluronic acid injection solely in the temple region. A 40-year-old woman, 3 hours after the procedure, presented to our hospital with left eye ophthalmoplegia, ptosis, and hypotropia. Treatment started with hyaluronidase, steroids, and anticoagulants. After 4 weeks, left eye ophthalmoplegia remained unchanged, and through a 10-week follow-up, all left ocular movements improved, and only mild hypotropia and ptosis persisted. This case report shows that ophthalmoplegia may also happen with temple region filler injections. We also review available prevention techniques and treatments to avoid such complications when performing soft tissue fillers for gaunt appearance correction.
Keywords: ophthalmoplegia; surgery; plastic; hyaluronic acid; cosmetics